Participatory Learning and Action untuk Edukasi Stunting dan Pencegahan Pergaulan Bebas di MTs Al-Mu’min Desa Dogang - M. Rafli Lingga; Siti Khairani Maisyaroh; Farida Berliana; Ibnu Radwan Siddik Turnip (BADAN PENERBIT STIEPARI PRESS, 2025)
The 2025 Community Service Program (KKN) of UIN Sumatera Utara in Dogang Village, Langkat Regency, aimed to increase adolescents’ awareness of nutrition and reproductive health through education on stunting and the prevention of risky behaviors. This activity applied the Participatory Learning and Action (PLA) approach, which emphasizes active involvement of participants. The preparation stage included coordination with the school, development of educational modules, and preparation of learning media such as slides and videos. The implementation involved MTs Al-Mu’min students in grades VII–IX through short lectures, group discussions, and role play to simulate real-life situations such as choosing nutritious food or refusing risky social interactions. Evaluation was conducted through oral questions and participant reflection. The results showed an improvement in adolescents’ understanding of stunting which was previously perceived only as a height issue as well as increased awareness of the risks of promiscuity. Students demonstrated enthusiasm and active participation, as reflected in critical questions and positive responses from both teachers and peers. This activity indicates that PLA is an effective educational method within the KKN program of UIN Sumatera Utara, not only in transferring knowledge but also in fostering critical awareness and adolescents’ skills in making healthy decisions.